Strategies For Endangered Language Preservation Throughg Blockchain And Tecnology In SD Negeri 064023 Kemenangan Tani, Academic Year 2025/2026 - Silaban, Roikestina; Nababan, Rosma; Supriadi, Supriadi; Arisetya, Dian (Program Studi Pendidikan Biologi, 2025)
This study aimed to explore strategies for preserving endangered local languages through the integration of blockchain and digital technology in elementary school. The research was conducted at SD Negeri 064023 Kemenangan Tani academic year 2025/2026. The study focused on how technology-based learning could be designed to strengthen students’ awareness and participation in protecting linguistic heritage. A qualitative descriptive approach was employed, involving classroom observations, teacher interviews, and documentation analysis. The findings indicated that blockchain technology provided a secure digital framework for recording, storing, and sharing local language materials, ensuring authenticity and preventing data loss. Digital storytelling and multimedia platforms enhanced students’ engagement and speaking confidence while learning local linguistic elements. The implementation of this digital preservation model encouraged collaboration between teachers, students, and the local community. It also fostered a sense of cultural identity and pride among young learners. The study concluded that integrating blockchain and digital media in the elementary classroom represented an innovative and sustainable approach to language preservation in the global digital era. These strategies not only supported pedagogical goals but also contributed to cultural resilience and digital literacy at the primary school level.